2021
DOI: 10.1155/2021/8858836
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cardiac Resynchronization Therapy in Patients with a Narrow QRS Complex

Abstract: Aims. In the guidelines for cardiac resynchronization therapy (CRT), there is a gap between the Japanese Circulation Society (JCS) criteria, which specify a QRS duration of ≥120 ms, and other countries, with a QRS ≥ 130 ms. The efficacy of CRT remains controversial in patients with a narrow QRS <130 ms. The aims of this study are to evaluate the response to CRT in patients with a narrow QRS and to identify predictors of mortality. Methods. We retrospectively studied 212 patients who received CRT. They were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Our study also confirmed that overall survival is significantly better in NYHA class II or III heart failure compared with NYHA IV heart failure ( Fig. 1 ) [10] .…”
Section: Current Status Of Crtsupporting
confidence: 85%
“…Our study also confirmed that overall survival is significantly better in NYHA class II or III heart failure compared with NYHA IV heart failure ( Fig. 1 ) [10] .…”
Section: Current Status Of Crtsupporting
confidence: 85%
“…Critical variables such as global scar burden, scar location, lead position, programmed AV and VV interval, mitral regurgitation, and irreversibly advanced heart failure cases are imperative considerations to improve the outcome [20] Despite the traditional dogma that normal QRS duration is a contraindication for CRT, recent challenging groups suggest that QRS complex <130 ms might benefit from CRT. This response as they describe it, is personalized but having QRS complex <130 ms should not be a reason to withhold the option of CRT in systolic heart failure if no other effective treatment is available [21]. Despite the claim that CRT is under-utilized worldwide, we suggest more wise selections with the advanced criteria for more intelligent selection.…”
Section: The Dilemma Of Intelligent Resynchronization Therapy Subject...mentioning
confidence: 94%